RESPONS PENGELOLAAN KOLABORATIF TERUMBU KARANG DI DESA BILORO KABUPATEN BURU SELATAN - Tuhumury, Semuel F; Abrahamsz, James; Sahetapy, Dicky; Tetelepta, Johannes M.S.; Haulussy, Jalil (TRITON: Jurnal Manajemen Sumberdaya Perairan, 2021)
The use of the coral ecosystem causes a systemic impact on that ecosystem. There are various types of coral reef ecosystem utilization, and the management of this ecosystem, therefore, needs a collaborative approach. The objective of this study was to identify the condition of coral reef, to identify types of utilization and its impact on the coral reef ecosystem and produce a collaborative management response towards the coral reef ecosystem. The research was conducted n July 2020 at the coral reef area of Biloro Village, Sub-district of Kapala Madang, Southern Buru. Field observation uses the Line Intercept Transect method for coral reef condition assessment, while the PRA approach to identify trigger factors, stress against the environment, the impact, and strategic adaptive response management. The collaborative method is a strategic adaptive response that conveys the system concept of socio-ecology, community capacity, and institutional empowerment in management integration. The result shows that on average coral reef ecosystem was in good condition. There are five responses collaborative management proposed explicitly education advocacy in the importance of coral reef, rehabilitation of degraded coral reef, the establishment of community controlling group, village by law, and the development of Toumahu Island marine tourist. ABSTRAK Pemanfaatan ekosistem terumbu karang memberikan dampak sistematis. Pengelolaan terumbu karang pada lokasi penelitian membutuhkan pendekatan kolaboratif. Penelitian ini bertujuan mengindentifikasi kondisi karang, mengidentifikasi bentuk-bentuk pemanfaatan dan dampaknya serta respon pengelolaan kolaboratif ekosistem terumbu karang. Penelitian dilakukan pada bulan Agustus tahun 2020, pada kawasan terumbu karang Desa Biloro, Kecamatan Kapala Madan, Kabupaten Buru Selatan. Penelitian lapangan menggunakan metode LIT untuk mengidentifikasi kondisi terumbu karang, dan pendekatan PRA untuk mengidentifikasi faktor pemicu, tekanan terhadap lingkungan, status terumbu karang, dampak yang ditimbulkan, serta respon strategis dan adaptif. Pendekatan kolaboratif merupakan respon strategis-adaptif yang mengusung konsep sistem sosial-ekologis, penguatan kapasitas masyrakat, penguatan kelembagaan dalam pengelolaan, dan integrase pengelolaan. Hasil penelitian menunjukan secara-rata-rata kondisi terumbu karang Desa Biloro tergolong baik. Lima usulan pengelolaan respon kolaboratif berupa sosialisasi pentingnya terumbu karang, rehabilitasi terumbu karang, pembentukan POKWASMAS, pembuatan aturan desa, dan pengembangan wisata bahari Pulau Toumahu. KATA KUNCI: Terumbu karang, PRA, respon strategis-adaptif, pengelolaan kolaboratif, sistem sosial-ekologi